PENGARUH LATIHAN KELINCAHAN DAN LATIHAN KECEPATAN TERHADAP PENINGKATAN KEMAMPUAN DRIBBLING DALAM PERMAINAN SEPAKBOLA PADA SISWA ESKTRAKURIKULER SMP NEGERI 1 EREMERASA KABUPATAEN BANTAENG - Andi zulfiansyah mappamadeng; Irvan; Juhanis; Muhammad Kamal; Muh. Adnan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of agility and speed training on dribbling skills in extracurricular soccer students at SMP Negeri 1 Eremerasa, and to compare the effectiveness of both forms of training. This study used an experimental method with a Two Groups Pretest-Posttest Design. The results showed that both agility and speed training had a significant effect on improving dribbling skills